Overview of the European General Data Protection Regulation (GDPR) impact on medical writing for clinical trials - Revenco, Tatiana; Collet, Gregory (Medical writing (Leeds), 2023)
The European General Data Protection Regulation 2016/ 679 (GDPR) aims to ensure the security and privacy of individuals in the European Union (EU). Companies located within and outside of the EU must comply with GDPR when processing personal data of EU citizens. Medical writing includes the development of documents related to clinical research. To develop those documents, medical writers have access to personal data, including health information considered as sensitive data. Therefore, medical writing falls within the purview of GDPR and must comply with its requirements. This article is an overview of the impact of GDPR on medical writing including security measures such as anonymisation, pseudonymisation, and data minimisation techniques. It also provides an overview of the technical and organisational actions in the framework of medical writing to guarantee respect of data subjects’ rights and freedoms.